P107 Long-term adherence to exercise after pulmonary rehabilitation: Understanding the motivations and barriers to exercise?. (19th November 2012) - Lee, C; Elkin, S
Abstract : Introduction: Adherence to exercise after PR is known to be low and the role of motivation/barriers in this population remains unclear. This study aimed to further investigate the role of motivation and barriers to exercise and specifically profiling trends that may guide/assist maintenance strategies. Method: 112 (58=M) patients who completed >50% of a PR programme over a 3 year period, were sent a postal survey. Data collected included; demographics, co-morbidities, MRC, physical activity/exercise and motivation (21 items) and barriers (14 items) to exercise quantified along a 5 point-likert scale (Newson and Kemps, 2007). Results: 51.8% (n=58) responded; mean age 71.72, MRC dyspnoea 2.86 and co-morbidities 1.09, COPD=87.9%. Motivation and barriers were analysed separately, as mean motivation/barriers weren't significantly correlated. Mean barrier was significant correlated with MRC dyspnoea (p=0.003), co-morbidities (p<0.001) and intent to exercise (p<0.001), but not with motivation. Sub-analyses identified those who exercised regularly (currently at least once a week most weeks) rated motivations and barriers significantly different to those who didn't. Exercisers had significantly higher mean motivation (p=0.023) and deemed the following factors to be significantly more motivating reasons to exercise; 'I want to be physically fit' (p=0.002); 'I exercise because a health professional advised me to' (p=0.029); 'I want to stay in shape' (p=0.019) and 'exercising gives me energy' (p=0.0210). Conversely the non-exercisers had significantly higher mean barrier score (p=0.003) and rated the following as significantly greater barriers; 'Shortness of breath' (p=0.013); 'lack of energy' (p=0.011); 'having a limited health/physical condition' (p=0.028); 'painful joints' (p=0.002); 'not knowing what you are capable of, or should be doing' (p=0.030); fear of, injury (p=0.032), falling (p=0.036) and safety (p=0.021). None of these factors changed over time since completing PR. Conclusion: This study quantified 21 motivating factors to exercise and 14 barriers that prevent exercise in the post-PR population. Some factors were rated significantly differently between exercisers and non-exercisers and did not significantly vary over time since completion of PR. Further research is required to establish if targeting specific factors could guide/assist maintenance strategies.